Service Quality and Brand Loyalty of Banks in Bayelsa State of Nigeria - M. Etale and Emmanuel N. Jerry, Lyndon (British Journal of Marketing Studies, 2022)
Citation: Lyndon M. Etale and Emmanuel N. Jerry (2022) Service Quality and Brand Loyalty of Banks in Bayelsa State of Nigeria, British Journal of Marketing Studies Vol. 10, Issue 1, pp.47-63The study was embarked upon with the aim of determining the nature of the relationship between service quality and brand loyalty of banks in Bayelsa State of Nigeria, and this was done using responsiveness and reliability as dimensions of service quality and brand advocacy as a measure of brand loyalty, bringing about two research questions and study hypotheses which was put to the test by the use of the Pearson correlation coefficient method with the aid of SPSS software. The study adopted the descriptive design and used a questionnaire as a means of gathering data from the customers of selected banks in Bayelsa State amounting to a total of 140, but a total of 130 copies of the questionnaire were retrieved and used for the analysis of data which informed the conclusion and findings of the research. The study revealed a significant relationship between both reliability and responsiveness as dimensions of service quality and brand advocacy as a measure of brand loyalty. The study therefore concluded that there is a significant relationship between the variables and thus made the following recommendations; Banks should give prompt and quick response to its customers? compliant by creating a simple and fast compliant handling system; Banks must let its customers feel safe and secured in any transaction; Banks should create a strong feedback system that enables them to relate effectively with customers and understand them better; Banks should fasten their service processes.